2019
DOI: 10.1111/jace.16739
|View full text |Cite
|
Sign up to set email alerts
|

Vacancy‐ and doping‐dependent electronic and magnetic properties of monolayer SnS2

Abstract: We have performed first‐principles calculations to investigate the formation and migration of vacancies and doping with M (M = Ti, V, Co, Mo, W, Re) at the Sn sites and X (X = O, Se, Te) at the S sites in monolayer SnS2. We find that the formation energies for S vacancy under both Sn‐ and S‐rich environments are lower than those for Sn vacancy, indicating that the vacancies at the S sites are likely to be formed during the synthesis. Reducing the possibility of vacancy cluster formation, both the vacancies at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 60 publications
(157 reference statements)
1
13
0
Order By: Relevance
“…The large surface area and weak out‐of‐plane van der Waals (vdW) interactions in these materials, can overcome the current challenges of poor electronic conductivity and damaging volumetric fluctuations during the intercalation and de‐intercalation. These materials, therefore, can find applications as various components of LIBs and sodium‐ion‐batteries (SIBs), including electrolytes, separators, as well as electrodes 20‐24 . Interestingly, the first rechargeable LIB, marketed by Exxon in the 1970s, consisted of the TMD, TiS 2 , as the cathode 25 .…”
Section: Introductionmentioning
confidence: 99%
“…The large surface area and weak out‐of‐plane van der Waals (vdW) interactions in these materials, can overcome the current challenges of poor electronic conductivity and damaging volumetric fluctuations during the intercalation and de‐intercalation. These materials, therefore, can find applications as various components of LIBs and sodium‐ion‐batteries (SIBs), including electrolytes, separators, as well as electrodes 20‐24 . Interestingly, the first rechargeable LIB, marketed by Exxon in the 1970s, consisted of the TMD, TiS 2 , as the cathode 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, elemental doping and nanoarchitecture engineering have been employed to tune the electronic structures and the exposed edge sites to improve the gas physisorption and sensing characteristics of pure SnS 2 . 24 For instance, Ou et al reported the synthesis of SnS 2 planar nanodisks by a facile oil-phase method, showing the high NO 2 -sensing response at 160 °C due to the facilitated physisorption and rich active edge sites. 25 The physisorption always presents weak selectivity to different adsorbates, whereas a synergy with chemisorption will be highly desired for the selective sensing.…”
Section: ■ Introductionmentioning
confidence: 99%
“…One representative example was the SnS 2 /SnO 2 heterostructure wherein the SnS 2 –SnO 2 interface played a vital role for the gas adsorption and NH 3 -sensing performance. , However, the uneven distribution of the interface may impose an obstacle in the regulation of sensing behaviors and the precise understanding of interface effects. Alternatively, elemental doping and nanoarchitecture engineering have been employed to tune the electronic structures and the exposed edge sites to improve the gas physisorption and sensing characteristics of pure SnS 2 . For instance, Ou et al reported the synthesis of SnS 2 planar nanodisks by a facile oil-phase method, showing the high NO 2 -sensing response at 160 °C due to the facilitated physisorption and rich active edge sites .…”
Section: Introductionmentioning
confidence: 99%
“…In practical situations, some researchers simplify the form of the diffusion pre-factor as D 0 = a 2 ν */2 with ν * given by the Debye frequency of the system. 169–171…”
Section: Ionic Diffusionmentioning
confidence: 99%